Exosomal MicroRNA-9-3p Secreted from BMSCs Downregulates ESM1 to Suppress the Development of Bladder Cancer - Hongzhou Cai; Xuejian Yang; Yang Gao; Zicheng Xu; Bin Yu; Ting Xu; Xiao Li; Weizhang Xu; Xinwei Wang; Lixin Hua (Elsevier, 2019)
Exosomes, carriers to transfer endogenous molecules, derived from bone marrow-derived mesenchymal stem cells (BMSCs) have been reported to play a role in the progression of bladder cancer. Here we aimed to test the functional mechanism of microRNA-9-3p (miR-9-3p)-containing exosomes derived from BMSCs in bladder cancer. BMSCs were cocultured with bladder cancer cells, and exosomes secreted from BMSCs were identified. Next, the expression of miR-9-3p and endothelial cell-specific molecule 1 (ESM1) in bladder cancer tissues and cells was determined. Then effects of miR-9-3p and ESM1 via BMSC-derived exosomes on bladder cancer cell viability, migration, invasion, and apoptosis were determined by loss- and gain-of-function experiments and on in vivo tumor growth, and metastasis was assessed in nude mice. miR-9-3p expression was decreased and ESM1 was increased in bladder cancer. BMSCs inhibited bladder cancer cell viability, migration, and invasion, and induced apoptosis, whereas the addition of exosome secretion inhibitor GW4869 achieved the opposite effects. Moreover, exosomal miR-9-3p upregulation or ESM1 silencing suppressed bladder cancer cell viability, migration, and invasion; induced cell apoptosis; and inhibited in vivo tumor growth and metastasis. Taken together, BMSC-derived exosomal miR-9-3p suppressed the progression of bladder cancer through ESM1 downregulation, offering a potential novel therapeutic target for bladder cancer therapy. : Decreased miR-9-3p expression in bladder cancer reduces the inhibitory effect on endothelial cell-specific molecule 1 (ESM1). Increased ESM1 expression promotes bladder cancer cell proliferation, invasion, and metastasis, and inhibits apoptosis. miR-9-3p-containing exosomes secreted by bone marrow-derived mesenchymal stem cells (BMSCs) decrease the expression of ESM1, and hence inhibit bladder cancer cell proliferation, invasion, and metastasis, and promote apoptosis. Keywords: microRNA-9-3p, bone marrow-derived mesenchymal stem cells, endothelial cell-specific molecule 1, bladder cancer, exosome